Bacterial Pectinases and their Potent Biotechnological Application in Fruit Processing/Juice Production Industry: A Review - V. Suneetha*, K. Prathyusha and (Journal of Phytology, 2011)
Pectinases from food and food Bio products processed waste alone account to a total of one-third quarter of world’s food enzyme production. The uninterrupted search, which is being undergone for pectin hydrolyzing enzymes from biomass of fruit industry waste rich in lingo cellulosic material, is deriving straightaway immenseness in production of bacterial Pectinases .By products or waste obtained from orange, apple, grapes, pine apple, papaya, lemon juice manufacturing industries are used as source of the enzyme production .Scrutinized samples of soil obtained from fruit processed area are found to an appreciable reservoir for Pectinolytic Bacteria. The central theme of the review concentrates around the brief introduction to classified Pectinases, Pectinolytic Bacteria and different Pectinases employed at different stages of fruit juice processing. It also adds note on currently available commercial Pectinases.